2015
DOI: 10.4103/1463-1741.155848
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to music and noise-induced hearing loss (NIHL) among professional pop/rock/jazz musicians

Abstract: Noise-induced hearing loss (NIHL) has been extensively studied in industrial work environments. With the advent of new technologies, loud music has been increasingly affecting listeners outside of the industrial setting. Most research on the effects of music and hearing loss has focused on classical musicians. The purpose of the current study was to examine the relationship between the amount of experience a professional pop/rock/jazz musician has and objective and subjective variables of the musician's hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 14 publications
2
28
0
1
Order By: Relevance
“…This finding was consistent with previous studies and indicated the dose-response effect 18) . Moreover, hearing loss was more frequent in men than in women.…”
Section: Discussionsupporting
confidence: 94%
“…This finding was consistent with previous studies and indicated the dose-response effect 18) . Moreover, hearing loss was more frequent in men than in women.…”
Section: Discussionsupporting
confidence: 94%
“…The outcome of the current study showed that almost half of the total young participants were at mild risk of lifestyle induced hearing loss and approximately 40% of the participants were at moderate risk of lifestyle induced hearing loss. The findings of present study are in consonance with previous literature reported risk of hearing loss due to current lifestyle of youth [2][3][4][5][6]. The outcome of the present study showed younger adults at risk of lifestyle induced hearing loss.…”
Section: Discussionsupporting
confidence: 92%
“…In another study by Curhan et al [5] concluded that higher body mass index and larger waist circumference due to inappropriate diet chart are associated with increased risk of hearing loss in women. Halevi et al [6] investigated self-assessment of hearing loss in among professional pop/rock/jazz musicians. The outcome of their study showed that greater musical experience was positively linked to higher hearing thresholds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIHL has been found in symphony orchestra musicians [17], in rock musicians [15], and in other professional musicians [18, 19]. Pawlaczyk-Łuszczynska et al [16] assessed the hearing of 126 orchestra musicians and found 35% displayed high-frequency notches typical for NIHL, mainly at 6,000 Hz.…”
Section: Introductionmentioning
confidence: 99%